PENINGKATAN KEMAMPUAN MEMBACA MEMINDAI MELALUI PENDEKATAN COOPERATIVE LEARNING TIPE JIGSAW II DI KELAS V SEKOLAH DASAR NEGERI 08 PADANG BESI KOTA PADANG - randi eka putra, refril dani (Jurnal Tunas Pendidikan, 2021)
This research starts from the reality in the field, namely the scarcity of using approaches in learning and the lack of use of learning resources and tools. This is caused by learning that is still conventional so that students are less interested in participating in learning. For this reason, the authors are interested in improving the process of learning to scan reading in Indonesian language learning through the implementation of Classroom Action Research (CAR) using a Jigsaw II type cooperative learning approach. This Jigsaw II type cooperative learning approach is a learning approach that provides opportunities for students to think and discuss with friends to make themselves "experts" so that they can explain the material they discuss in expert groups to their friends in cooperative groups (origin), so that in learning students play an active role and the teacher acts as a facilitator. The purpose of this CAR is to describe the form of planning, form of implementation, and form of student learning assessment using the Jigsaw II type cooperative learning approach in learning to read and scan. This type of research is CAR (Classroom Action Research), research using quantitative and qualitative approaches. The subjects in this study were fifth grade students at SDN 08 Padang Besi, Padang City. The research data was obtained by using field notes, observations, and evaluations (tests). The results of each cycle carried out in this study showed an increase in students' reading and scanning skills from the evaluation of the first cycle of actions, the average percentage of students was 65%, while in the second cycle of action evaluation the average percentage was 78%. The results of the observations showed an increase in student activity in the learning process. So it can be concluded in this study that using a Jigsaw II type of cooperative learning approach can improve students' scanning reading skills.